Facial misidentifications arise from the erroneous activation of visual face memory. (October 2015) - Wirth, Benedikt Emanuel; Fisher, Katie; Towler, John; Eimer, Martin
Abstract: Misidentifications are a common phenomenon in unfamiliar face processing, but little is known about the underlying cognitive and neural mechanisms. We used the face identity-sensitive N250r component of the event-related brain potential as a measure of identity-sensitive face matching process in visual working memory. Two face images were presented in rapid succession, and participants had to judge whether they showed the same or two different individuals. Identity match and mismatch trials were presented in random sequence. On similar mismatch trials, perceptually similar faces of two different individuals were shown, while two physically distinct faces were presented on dissimilar mismatch trials. Misidentification errors occurred on 40% of all similar mismatch trials. N250r components were elicited not only in response to an identity match, but also on trials with misidentification errors. This misidentification N250r was smaller and emerged later than the N250r to correctly detected identity repetitions. Importantly, N250r components were entirely eliminated on similar mismatch trials where participants correctly reported two different facial identities. Results show that misidentification errors are not primarily a post-perceptual decision-related phenomenon, but are generated during early visual stages of identity-related face processing. Misidentification errors occur when stored representations of a particular individual face in visual working memory are incorrectly activated by a perceptual match with a different face. Highlights: N250r components are triggered when similar unfamiliar faces are misidentified. The N250r is smaller and delayed for false versus correct face identifications. No N250r is present when two similar faces are judged to be different. Misidentification errors are linked to incorrect activations of visual face memory.